Developing English for Tourism and Hospitality Materials Based on Banyuwangi Local Needs - Nurhalimah; Reni Nur Jannah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2022)
The Ministry of Education and Culture stepped up the connect-and-matcheffort by creating a teaching factory to combine vocational education withthe industrial world. The program's goal is to increase the number ofgraduates from vocational schools who are employed as trained and qualifiedhuman resources (HR) to meet the demands of the sector. The suitability andrelevance of the material to local needs, especially in the world of tourism inBanyuwangi should be included in the learning materials. In order toestablish a link and match, it is required to conduct a thorough examinationof the development of learning instruments. The purpose of this study is todevelop English for Tourism and Hospitality teaching materials inaccordance with the local needs of the tourism industry in Banyuwangi.This research was an R & D (Research and Development) using the ADDIEmodel. The results showed that the English for Tourism and Hospitalitymaterials that would be applied to the Tourism Business Management StudyProgram, Banyuwangi State Polytechnic were relatively varied and diversewhich was divided into two parts, namely materials that reflect theBanyuwangi local culture such as Gedhogan, Kemiren, Gandrung Sewu,Barong Kemiren, Seblang Dance, Ngopi Sepuluh Ewu, Ijen Blue Fire,Tumpeng Sewu Festival, Red Island, as well as additional materials relatedto hospitality such as Hotel, Restaurant, and Travel Agent.